Community empowerment through making maroca (mangrove root craft) in village Tanjung Rejo, Kecamatan Percut Sei Tuan, Sumatera Utara - Enggar Susetya, Ipanna; Dewinta, Astrid Fauzia; Rambey, Ridahati; Sudiati, Sudiati; Azhari, Azhari; Suriani, Mai (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Mangrove ecosystems in Tanjung Rejo Village, Percut Sei Tuan Sub-district, Deli Serdang experienced a lot of land conversion in the form of residential, agricultural and plantation lands. This causes abrasion in this region because there is no protection from waves and sea waves in this region. Land conversion and abrasion caused many mangrove trees to die. Mangrove trees that died were only used on the trunk, twigs and leaves by local residents. Many parts of the dead mangrove roots are not utilized. This community service activity aims to provide information and skills to partner groups about the making of MAROCA. Through this activity, partners will gain knowledge and skills in making MAROCA so that materials that are not initially valuable like dead mangrove roots become useful. Based on the description of the problem and the purpose of this community service activity, the activities that have been carried out are counseling about the manufacturing of MAROCA, giving leaflets for the procedures for making and providing tools and materials. The results obtained are increased knowledge and skills of partners about the benefits of dead mangrove roots as economically valuable handicrafts.